STRATEGIC PLANNING AND INSTITUTIONAL EVALUATION: MANAGEMENT TOOLS FOR EDUCATIONAL EXCELLENCE - Costa, Karina Ferreira Vicente (LUMEN ET VIRTUS, 2024)
This article explores strategic planning methodologies applied to school management and presents pedagogical performance indicators essential for institutional evaluation. It discusses how strategic planning frameworks enable educational leaders to define clear objectives, allocate resources effectively, and engage stakeholders in continuous improvement. The paper emphasizes the relevance of integrating performance indicators into institutional assessment to monitor quality and guide decision-making. Highlighting the close relationship between strategic planning and leadership in education, the article demonstrates how these management tools foster school excellence, support the development of school pedagogical projects (PPPs), and enhance internal regimentation processes, reflecting both technical and administrative competencies.